Chronic Obstructive Pulmonary Disease Patients have A Higher Risk of Developing Gastroesophageal Reflux Disease than the General Population A-Multi-Center-Study - Muhammad Mudasir, Imran Ullah, Obaid Ur Rehman, Talha Durrani, Faheem Ur Rahman (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Partially reversible airflow restriction is a symptom typical of COPD, a kind of obstructive lung disease. Chronic obstructive pulmonary disease distinct pathological and clinical phenotypes: emphysema and chronic bronchitis (COPD). Both elements are quite individualistic. Whether or not to regularly examine COPD patients for the possibility of GERD and treat it effectively might be aided by the discovery of an increased prevalence of Gastroesophageal reflux disease (GERD) in this patient population. Objective: As GERD is associated with a worse prognosis in COPD patients, it is important to understand the prevalence of this condition among those who suffer from the disease. Methodology: From January 2021 to January 2022, researchers at a major hospital in Peshawar analyzed data from many similar hospitals. A total of 108 participants participated in this trial. Comprehensive histories and physical examinations were performed on patients (aged 20 to 75). Then, spirometry and the Q-questionnaire were administered to individuals who had satisfied the inclusion and exclusion criteria. All patients had their spirometry readings taken by the same CPSP-certified technicianpatients’ FEV1 measurements following a bronchodilator treatment were assessed by the same CPSP-fellow consultant of pulmonology using the GOLD criteria, giving each patient a grade (from "01" to "04"). The prevalence of GERD was calculated as a percentage of all COPD cases in patients who completed the Q-questionnaire. Results: There was a 12.580 standard variation in the individuals’ ages, with a mean of 58.76. Most patients were women (60%), while men made up just 40% of the Total. The prevalence of GERD among those with COPD was 52 percent. Conclusion: This study’s findings led us to conclude that patients with COPD had a frequency of gastroesophageal reflux disease (GERD), which was 52%. Keywords: Acid Reflux In The Stomach; COPD, Multicenter